Firm provision of general training and specific human capital acquisition - Casas-Arce, P (University of Oxford, 2004)
The existing literature on training is concerned with understanding the reasons why firms pay for the general skills of their workers, but without explaining which firms train which workers. This paper develops a theory that both explains the willingness of firms to pay for general training, and accounts for the pattern of training provision empirically observed. It is assumed that labor markets are perfectly competitive, but there is imperfect contractibility of human capital. Under these assumptions, when training and specific human capital are complements, the firm would pay for the former in order to induce the acquisition of complementary specific skills by the worker.